Missionary methods : St. Paul's or ours? - Allen, Roland, 1869-1947. (Grand Rapids, Mich : Wm B. Eerdmans Pub. Co., 1962)
We are talking today of indigenous churches. St. Paul's churches were indigenous churches in the proper sense of the word; and I believe that the secret of their foundation lay in his recognition of the church as a local church (as opposed to our "national churches") and in his profound belief and trust in the Holy Spirit indwelling his converts and the churches of which they were members, which enabled him to establish them at once with full authority. - Author's preface to the second (1927) edition.
Foreword / Lesslie Newbigin -- Publisher's foreword -- Author's preface -- Part 1 : Antecedent conditions. Introduction -- Strategic points -- Class -- Moral and social condition -- Part 2 : The presentation of the gospel. Miracles -- Finance -- The substance of St. Paul's preaching -- Part 3 : The training of converts. The teaching -- The training of candidates for baptism and ordination -- Part 4 : St. Paul's method of dealing with organized churches. Authority and discipline -- Unity -- Part 5 : Conclusions. Principles and spirit -- Application -- Epilogue.
Companion volume to the author's The spontaneous expansion of the church.
Keywords: Paul, -- the Apostle, Saint; Missions